Fabrication and Characterization of Air-Stable Organic-Inorganic Bismuth-Based Perovskite Solar Cells. (26th June 2018) - Sanders, S.; Stümmler, D.; Pfeiffer, P.; Ackermann, N.; Simkus, G.; Heuken, M.; Baumann, P. K.; Vescan, A.; Kalisch, H.
Abstract: Pb-based organometal halide perovskite solar cells have passed the threshold of 20 % power conversion efficiency (PCE). However, the main issues hampering commercialization are toxic Pb contained in these cells and their instability in ambient air. Therefore, great attention is devoted to replace Pb by Sn or Bi, which are less harmful and - in the case of Bi - also expected to yield enhanced stability. In literature, the most efficient hybrid organic-inorganic methylammonium bismuth iodide (MBI) perovskite solar cells reach PCE up to 0.2 %. In this work, we present spin-coated MBI perovskite solar cells and highlight the impact of the concentration of the perovskite solution on the layer morphology and photovoltaic (PV) characteristics. The solar cells exhibit open-circuit voltages of 0.73 V, which is the highest value published for this type of solar cell. The PCE increases from 0.004 % directly after processing to 0.17 % after 48 h of storage in air. 300 h after exposure to air, the cells still yield 56 % of their peak PCE and 84 % of their maximum open-circuit voltage.